The Influence of Matrix Chemical Structure on the Mode I and II Interlaminar Fracture Toughness of Glass-Fiber/Epoxy Composites - Alvarez, Vera Alejandra (2003)
The present paper is concerned with Mode I and Mode II delamination tests performed on three different glass fiber reinforced epoxy composites, chosen to obtain different final structures. The effect of crosshead speed on the fracture resistance of the composites was also analyzed. It was found that Mode I propagation values (GIC) increase as the crosshead speed decreases, probably because of the increase of brittleness in the studied range. An Arrhenius type relation between GIC and the glass transition temperature of the epoxy resin/amine system (Tg) was found. Mode II initiation values (GIICinit) and apparent shear strength (SH) were found to increase with the decrease of Tg. The relation between matrix toughness and composite interlaminar fracture toughness was also considered. Finally, the GIC propagation values were compared to the data available In literature for similar materials.